Inorganic synthesis a manual for laboratory experiments - Gerasimchuk, Nikolay (Cambridge Scholars Publishing, 2019)
This book is designed to develop important practical skills for chemistry majors interested in synthetic chemistry. It will serve to teach students proper techniques for the preparation and handling of a variety of inorganic and coordination compounds. It shows them how to conduct thermal decomposition reactions; prepare moderately air-sensitive and moisture-sensitive compounds; and characterise obtained metal complexes using a variety of physical methods. This volume is well-illustrated with colour photos, schemes and figures that allow safe, step-by-step work on assigned laboratory experimen.